Numerical modelling of hydrodynamic and morphodynamic response of a meso-tidal estuary inlet to the impacts of global climate variabilities - Harshinie Karunarathna (Marine Geology, 2019)
Tidal inlets, a common feature along coastlines globally, can be significantly affected by the impacts of global climate variabilities. Computational models provide the best opportunity to assess future changes to the dynamics of inlet systems. In this paper, the morphodynamic response of a gravel-dominated meso-tidal estuary inlet to Sea Level Rise (SLR) is discussed based on three future SLR scenarios. It uses a process-based computational coastal area model. The study's test site is the meso-tidal Deben Estuary inlet in the UK; it is very morphodynamically active and has a unique sediment environment, is used as the test site of this study. The modelling results reveal that the morphological response of Deben inlet is sensitive to the SLR scenario. Rising sea levels give rise to increased hydrodynamic and morphodynamic activities at and around the inlet. The ebb delta, which is a prominent morphodynamic feature of this inlet, shows greater instability as a result of increased sea levels. It is possible that the inlet may deviate significantly from its current morphodynamic regime in the future as a result of the changes imposed by higher sea levels.